DISP-05. SOCIAL DETERMINANTS OF HEALTH AND INPATIENT SPINE TUMOR OUTCOMES: A NATIONWIDE ANALYSIS OF DISPARITIES FROM 2002-2019. (14th November 2022) - Tang, Oliver; Ayala, Cameron; Feler, Joshua; Perla, Krissia Rivera; Bajaj, Ankush; Ganga, Arjun; Fridley, Jared; Toms, Steven; Gokaslan, Ziya; Sullivan, Patricia Zadnik
Abstract: BACKGROUND: Earlier research has demonstrated that social determinants of health (SDoH) impact neuro-oncology access and outcomes, influencing patient disparities. This study aimed to elucidate the association between SDoH and inpatient spine tumor outcomes. METHODS: All admissions with a spine tumor diagnosis in the National Inpatient Sample from 2002-2019 were identified. Four SDoH were analyzed: race and ethnicity, insurance, household income, and safety-net hospital (SNH) treatment. Hospitals in the top quartile of safety-net burden (percentage of patients receiving Medicaid or uninsured) were categorized as SNHs. Multivariable regression queried the association between 22 variables (patient, hospital, tumor, and severity characteristics) and six inpatient outcomes: mortality, discharge disposition, complications, length of stay (LOS), and hospitalization costs. Relative importance of predictors for discharge disposition were assessed using random forest models. RESULTS: Of 6, 593, 391 total admissions with spine tumors, 219, 380 (3.3%) underwent surgical intervention. Non-white race (odds ratio [OR] = 0.80–0.91, P = 0.001) and non-private insurance (OR = 0.76–0.83, P = 0.001) were associated with lower odds of surgery. Among surgical admissions, presenting severity, including myelopathy and plegia, was elevated among nonwhite, non-private insurance, and low-income admissions (all P = 0.001). Black race (OR = 0.70, P = 0.001), Medicare (OR = 0.70, P = 0.001), Medicaid (OR = 0.90, P=0.001), and lower income (OR = 0.88–0.93, all P = 0.001) were associated with decreased odds of favorable discharge disposition. Elevated LOS and costs were observed among non-white (LOS: +6-10%, costs: +5-9%, both P = 0.001) and Medicaid (LOS: +16%, costs: +6%, both P = 0.001) admissions. SNH treatment was also associated with higher mortality (OR = 1.49, P = 0.001) and complications (OR = 1.20, P = 0.001). From 2002-2019, disposition improved annually for Medicaid patients (OR = 1.03 per year, P = 0.022) but worsened for Black patients (OR = 0.98 per year, P = 0.046). Random forest models identified household income as the most important disposition predictor. CONCLUSION: For spine tumor admissions, SDoH predicted surgical intervention, presenting severity, and perioperative outcomes. Over two decades, disparities improved for Medicaid patients but worsened for Black patients.